A STUDY ON THE USE OF TARGET AND MIXED LANGUAGES IN COMMUNICATION STRATEGIES IN TEACHING ENGLISH AT SMP NEGERI 1 SINGARAJA - Y, Dewi; Batan, I.G.; Mahayanti, N.W.S. (Universitas Pendidikan Ganesha, 2018)
The use of target language only and mixed languages as communication strategies between the teacher and students have different purposes to be achieved for both of them when conducting the learning process. Therefore, this study focused on finding out 1) the language of instruction used by the teacher as communication strategies in teaching as well as 2) the student’s responses toward the use of each type of language of instruction as communication strategies in teaching English by the teacher at SMP Negeri 1 Singaraja. To investigate this study there were 3 teachers and 174 students from eight classes who were used as the primary sources. To collect all of the data, observation and questionnaire distribution were implemented. Then, all of the data were analyzed descriptively. This study followed qualitative descriptive model, approach, and design adopting framework of Maxwell (2012). Therefore, the results of the study indicates that the most frequent of language uses by the teachers is target language only. The students fell very glad when the teachers use target language only. To make the students easier to understand the material, the use of mixed languages in the right portion is very good, in particular at the beginning stages. Key words: target language, mixed languages, opening, observing, questioning, exploring, associating, communicating, closing.